1994
DOI: 10.1523/jneurosci.14-11-06598.1994
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent reduction of tissue loss and functional impairment after spinal cord trauma with the AMPA/kainate antagonist NBQX

Abstract: Initial studies on the role of glutamate receptors in traumatic spinal cord injury (SCI) implicated the NMDA subclass of ionotropic glutamate receptors in contributing to functional deficits. Recently we obtained evidence suggesting that non-NMDA ionotropic receptors may participate in producing a portion of the behavioral impairment after SCI. To test this hypothesis we have conducted a dose-response experiment, focally injecting 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo(f)quinoxaline (NBQX; 1.5, 5, or 15 nmol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
121
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(140 citation statements)
references
References 55 publications
(88 reference statements)
14
121
1
1
Order By: Relevance
“…Several lines of evidence have suggested that glutamate excitotoxicity plays a key role not only in neuronal cell death but also in delayed post traumatic spinal cord white matter degeneration (Faden and Simon, 1988;Wrathall et al, 1994;Agrawal and Fehlings, 1997;Wrathall et al, 1997). Oligodendrocytes are highly vulnerable to excitotoxic signals mediated by glutamate receptors of the AMPA and kainate classes compared to astrocytes (Oka et al, 1993;Yoshioka et al, 1996;Agrawal and Fehlings, 1997;Matute -27 -et al, 1997;McDonald et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have suggested that glutamate excitotoxicity plays a key role not only in neuronal cell death but also in delayed post traumatic spinal cord white matter degeneration (Faden and Simon, 1988;Wrathall et al, 1994;Agrawal and Fehlings, 1997;Wrathall et al, 1997). Oligodendrocytes are highly vulnerable to excitotoxic signals mediated by glutamate receptors of the AMPA and kainate classes compared to astrocytes (Oka et al, 1993;Yoshioka et al, 1996;Agrawal and Fehlings, 1997;Matute -27 -et al, 1997;McDonald et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…44 The administration of NBQX (a non-NMDA receptor antagonist) within 4 h of injury improves neurological prognosis. 45 Therefore, inhibition of post-traumatic glutamate release may be one of the possible mechanisms of the neuroprotective effect of hypothermia. Although systemic hypothermia has been reported to have a neuroprotective effect through inhibiting TPC, the pyramidal tract in rodents runs in ventral region of the dorsal column.…”
Section: Discussionmentioning
confidence: 99%
“…We show that the novel serine protease MSP is present at high levels in the normal brain and spinal cord and is upregulated severalfold in spinal cord neurons and glia by K A-mediated excitotoxic injury. There is considerable evidence for a role of non-NMDA receptors in the response of the spinal cord white and gray matter to injury (Gomez-Pinilla et al, 1989;Rothstein et al, 1993;Wrathall et al, 1994;Agrawal and Fehlings, 1997). Further, it has been demonstrated in vitro that spinal motor neurons are selectively vulnerable to AMPA/kainate receptor-mediated injury because of the expression of AMPA/kainate receptors gating channels with direct Ca 2ϩ permeability (Carriedo et al, 1996).…”
Section: Role Of Msp In the Response Of The Spinal Cord To Excitotoximentioning
confidence: 99%